PENGARUH MODEL COLLABORATIVE LEARNING TERHADAP MOTIVASI BELAJAR SISWA KELAS 3 SDN 095550 JL.ASAHAN DALAM MATA PELAJARAN MATEMATIKA - Simanjuntak, Melvin M; Diah Mareta Damanik; Putri Rahmadani; Suryaningsih Purba; Cindy Fatika Sari; Ester Damayanti Panjaitan; Siska Ananda Hutasoit; Yosua Pandiangan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe the effect of implementing the collaborative learning model on students' learning motivation in grade 3 Mathematics at SDN 095550 Jl.Asahan. Collaborative learning emphasizes cooperation between students to solve problems, share knowledge, and help each other in achieving learning goals. Collaborative learning can increase student motivation, engagement and overall learning outcomes. The results of the research show that the collaborative learning model has a positive and significant effect on increasing student motivation in grade 3 Mathematics at SDN 095550 Jl. Asahan. The results of the research can be concluded that the application of the collaborative learning model can be used by students in elementary school mathematics learning to increase student motivation and learning outcomes.